We love you, Bunny : a novel [large type] - Awad, Mona (Thorndike Press large print high octane., 2025)
"In the cult classic novel Bunny, Samantha Heather Mackey, a lonely outsider student at a highly selective MFA program in New England, was first ostracized and then seduced by a clique of creepy-sweet rich girls who call themselves 'Bunny.' An invitation to the Bunnies' Smut Salon leads Samantha down a dark rabbit hole (pun intended) into the violently surreal world of their off-campus workshops where monstrous creations are conjured with deadly and wondrous consequences. When [this follow-up] opens, Sam has just published her first novel to critical acclaim. But at a New England stop on her book tour,her one-time frenemies, furious at the way they've been portrayed, kidnap her. Now a captive audience, it's her (and our) turn to hear the Bunnies' side of the story. One by one, they take turns holding the axe, and recount the birth throes of their unholy alliance, their discovery of their unusual creative powers--and the phantasmagoricadventure of conjuring their first creation"--